Parent Expectations of an Elementary School Counsellor: A Concept-Mapping Approach - Paulson, Barbara L.; Edwards, Mark H. (Canadian Journal of Counselling and Psychotherapy, 2007)
A concept-mapping process was used to understand parental expectations of an elementary school counsellor's role. The 25 parents who participated generated 91 statements that were subsequently sorted by each parent and analyzed to develop a seven-theme conceptualization of parental expectations. Parents requested that the counsellor become highly involved in providing services that involve support, referral, education, and information. In addition to perceiving the counsellor as a provider of direct counselling services, parents expected that the school counsellor would collaborate extensively with them. Additional expectations include developmental programming for all children in the school and services involving teacher consultation, special needs programming, and community liaison.